Contributions shedding light on the character and work of the Archbishop - martyr Varlaam of Ohrid - Nedeski, Viktor (MANU, 2018)
This paper attempts to clarify some facets of the personality of an almost unknown archbishop of Ohrid, namely the holy neomartyr Varlaam, who suffered in the city of Veles in 1598. The occasion of the martyrdom is considered in the context of historical circumstances reconstructed on the basis of direct and indirect historical sources. This paper also attempts to answer the question: Why did the cult of St. Varlaam of Ohrid vanished?
Keywords: Varlaam of Ohrid, Neomartyr, Archbishop, John Vishensky